Sistem Informasi Monitoring Skripsi Berbasis Web (Studi Kasus: Prodi Akuntansi Universitas Mercu Buana) - Kristiyanti, Dinar Ajeng; Mulyana, Ahmad (Universitas Diponegoro, 2020)
One of the final requirements in academic education for students is to conduct scientific research as outlined in the form of a final thesis. The large number of students taking research courses, makes the Accounting Study Program of the Faculty of Economics and Business at Mercu Buana University difficult to monitor the implementation of the thesis in every semester. With this problem, the researcher aims to build an information system to monitor the thesis that can record all the processes from the beginning of choosing the topic, taking the thesis exam and the graduation done by students. The urgent need for the development of a thesis monitoring information system is the reason for choosing a method of developing Rapid Application Development (RAD), so that the wishes of the Head of Accounting Department of the Faculty of Economics and Business at Mercu Buana University can be fulfilled immediately. The RAD stage that has been carried out is the requirement gathering stage which covers the needs of the operational environment, functional requirements, information needs, and interface requirements. The design phase consists of conceptual schema design, database design and interface design. The result of this research is a thesis monitoring system which has been tested and applied to the Accounting Study Program at Mercu Buana University. This system helps for both students in thesis consultation and the head of accounting in monitoring thesis students effectively and efficiently.